2020
DOI: 10.33545/gynae.2020.v4.i5b.688
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of enhanced recovery after surgery (ERAS) versus non enhanced recovery after surgery (Non-ERAS) pathway for caesarean deliveries

Abstract: Enhanced recovery is to optimize multiple aspects of patient care to improve recovery thereby facilitating earlier discharge, without a reduction in patient satisfaction or the quality of care. Currently, there are limited randomized studies exist in the literature specifically addressing the potential impact of an enhanced recovery pathway among women undergoing caesarean delivery on postoperative outcomes and postoperative length of stay. The study was done to determine efficacy of ERAS in comparison with St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Patients in the ERAS group were encouraged to begin oral fluid intake upon arrival in the PACU, as contrasted with the control group, who first allowed oral intake 6 hours after PACU arrival. Junaidi et al 23 showed that early oral intake had no effect on PONV, but did promote earlier postoperative bowel function; spontaneous bowel empting was also significantly earlier in ERAS group in our series.…”
Section: Discussionsupporting
confidence: 38%
“…Patients in the ERAS group were encouraged to begin oral fluid intake upon arrival in the PACU, as contrasted with the control group, who first allowed oral intake 6 hours after PACU arrival. Junaidi et al 23 showed that early oral intake had no effect on PONV, but did promote earlier postoperative bowel function; spontaneous bowel empting was also significantly earlier in ERAS group in our series.…”
Section: Discussionsupporting
confidence: 38%
“…13 Similar outcomes were reported from India. 14 Focused and modified ERAS RCT by Madhumala et al has clearly demonstrated the benefit of early gut stimulation and postoperative nausea and vomiting although the end point of shorter postoperative hospital stay was not analyzed. 15 Early feeding as a focused postoperative component of ERAS in Pakistan showed favorable maternal outcomes.…”
Section: Clinical Settingmentioning
confidence: 99%
“…Despite the challenges, modified ERAS has also proven beneficial in limited‐resource settings. Only a few care flow processes in preoperative, intraoperative, or postoperative pathways were implemented based on the resources available 7–9 . These studies in low resource settings have clearly demonstrated the benefits in terms of early hospital discharge, lesser postoperative complications, readmission, and greater patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%